Running, identity and meaning : the pursuit of distinction through sport - Baxter, Neil (Emerald Studies in Sport and Gender, 2021)
Running, Identity and Meaning showcases how gender, class, age and ethnicity influence whether and how different groups participate in the sport, and explores its role in the reproduction of social structure and the search for distinction.